Weed Flora of Citrus Orchards and Factors Affecting its Distribution in Western Mediterranean Region of Turkey - ONEN,H. (2018)
ABSTRACT: Citrus is an important export commodity, mostly grown on Mediterranean and Aegean coasts of Turkey. Weeds are hidden foes impairing citrus productivity. Limited knowledge of weed distribution and factors affecting the distribution are among major hurdles in successful weed management. In this study, weed flora of citrus orchards and factors affecting its distributions in Mugla province of Turkey were determined. Sixty orchards were surveyed in spring and autumn seasons of 2010 and 2011. Data relating to frequency, coverage and density of weed species were recorded. Soil samples (0-30 cm depth) were collected and analyzed for physicochemical properties. Climatic variables, altitude and soil properties were correlated with weed flora. Sixty-eight weed species belonging to 30 families were documented. Higher number of weed species (54) was recorded in spring season compared with autumn (29 weed species). Annuals and therophytes were the most dominant growth and life forms, respectively. Canonical Correspondence Analysis (CCA) to correlate soil properties and weed vegetation data yielded three distinct groups dominated by phosphorus, sand and silt contents, which affected weed distribution. CCA to correlate vegetation data and weather attributes produced two distinct groups affected by altitude and precipitation. Generally, cosmopolitan weeds adapted to different ecosystems were observed during the survey. Keeping in view the spatial variability of soil and nature of weeds, site-specific/orchard-specific weed management practices are recommended to be opted for successful weed management.